2018
DOI: 10.1007/s00787-018-1244-7
|View full text |Cite
|
Sign up to set email alerts
|

Placebo response rates and potential modifiers in double-blind randomized controlled trials of second and newer generation antidepressants for major depressive disorder in children and adolescents: a systematic review and meta-regression analysis

Abstract: Children and adolescents with major depressive disorder (MDD) appear to be more responsive to placebo than adults in randomized placebo-controlled trials (RCTs) of second and newer generation antidepressants (SNG-AD). Previous metaanalyses obtained conflicting results regarding modifiers. We aimed to conduct a meta-analytical evaluation of placebo response rates based on both clinician-rating and self-rating scales. Based on the most recent and comprehensive study on adult data, we tested whether the placebo r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 82 publications
3
23
1
Order By: Relevance
“…Overall, the evidence from our meta-review is only partially in line with the current license status of antidepressants in children and adolescents. In fact, our findings support: (1) the current license of fluoxetine for MDD; (2) the approval of fluoxetine and sertraline for OCD [e.g., USA ( 1 ); UK ( 2 )]; (3) the lack of approval of antidepressants for ADHD. However, our results are in contrast with: 1) the absence of license for fluvoxamine and paroxetine for ADs [e.g., US ( 1 ), UK ( 2 ), France ( 23 )]; 2) the FDA approval of escitalopram for acute and maintenance treatment of depression ( 24 )]; 3) the license for fluvoxamine and clomipramine for OCD ( 1 ).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Overall, the evidence from our meta-review is only partially in line with the current license status of antidepressants in children and adolescents. In fact, our findings support: (1) the current license of fluoxetine for MDD; (2) the approval of fluoxetine and sertraline for OCD [e.g., USA ( 1 ); UK ( 2 )]; (3) the lack of approval of antidepressants for ADHD. However, our results are in contrast with: 1) the absence of license for fluvoxamine and paroxetine for ADs [e.g., US ( 1 ), UK ( 2 ), France ( 23 )]; 2) the FDA approval of escitalopram for acute and maintenance treatment of depression ( 24 )]; 3) the license for fluvoxamine and clomipramine for OCD ( 1 ).…”
Section: Discussionsupporting
confidence: 68%
“…For instance, in the USA, fluoxetine and escitalopram are Food and Drug Administration (FDA)-approved for major depressive disorder (MDD), fluoxetine, sertraline, fluvoxamine, and clomipramine for obsessive-compulsive disorder (OCD), duloxetine for generalized anxiety disorder (GAD) and the combination of olanzapine and fluoxetine for bipolar depression ( 1 ). In the UK, fluoxetine is licensed for MDD, fluvoxamine and sertraline for OCD, and imipramine for nocturnal enuresis ( 2 ). Furthermore, some antidepressants are used by clinicians for non-licensed indications, such as amitriptyline for neuropathic pain and, historically, TCAs, in particular imipramine, have been used for the management of attention-deficit/hyperactivity disorder (ADHD).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, the depression severity assessed via BDI also correlates only moderately with clinicial ratings using Hamilton Depression Rating Scale [ 40 ]. RCTs focussing on the effects of pharmacological antidepressants and/or psychotherapy have revealed larger effect sizes for both verum and placebo when clinician-based ratings were considered in comparison to self-ratings [ 41 - 43 ]. Accordingly, we recommend that future RCTs should include a clinician rating, ideally as the primary outcome as usual in pharmacotherapy trials, to answer the question whether vitamin D supplementation has antidepressant effects.…”
Section: Discussionmentioning
confidence: 99%
“…The median duration in 167 antipsychotic trials conducted over the last 60 years was 6 weeks, with a range of 3–28 weeks 4 . Although trial duration has been shown to influence some indications (i.e., Crohns), 5 in other conditions, the relationship between study duration and placebo response rate is less clear (i.e., in major depressive disorder (MDD)) 6 . In trials that use non‐traditional designs, like adaptive, 7 and placebo‐run‐in trial designs—developed to minimize the impact of increasing placebo response—it is hard to determine how much of the time on placebo can be contributed to historical control models 7 .…”
Section: Trial‐level Sources Of Heterogeneitymentioning
confidence: 99%